Surface treatment of solid electrolytes to reduce the interfacial resistance between the solid electrolyte and electrodes

By polishing and heat-treating Na-β''-alumina ceramic surfaces in an inert atmosphere, the interfacial resistance is reduced, allowing for high critical current densities, thus enabling fast-charging sodium batteries.

JP7618653B2Active Publication Date: 2025-01-21EMPA +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2022514726
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-09-04
Filing Date
2020-09-02
Publication Date
2025-01-21
Estimated Expiration
2040-09-02

AI Technical Summary

Technical Problem

The high interfacial resistance between ceramic solid electrolytes, such as Na-β''-alumina, and metallic sodium anodes in solid-state batteries limits the critical current density, hindering the development of fast-charging sodium batteries due to issues like poor sodium wetting and surface impurities.

Method used

A method involving polishing the surface of Na-β''-alumina ceramic followed by heat treatment in an inert atmosphere and applying pressure to enhance adhesion, resulting in an interfacial resistance of <10 Ωcm at room temperature and a critical current density of 12 mA/cm².

Benefits of technology

This approach significantly reduces interfacial resistance and increases critical current density, enabling fast-charging capabilities in solid-state sodium batteries, surpassing previous ceramic electrolytes like LLZO by achieving 10 times higher current densities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007618653000002
    Figure 0007618653000002
  • Figure 0007618653000003
    Figure 0007618653000003
  • Figure 0007618653000004
    Figure 0007618653000004
Patent Text Reader

Abstract

Sodium ion-conducting solid electrolytes, sodium battery electrodes, and electrochemical devices such as solid sodium metal batteries comprising these electrodes and solid electrolytes are disclosed. One exemplary method for preparing a sodium / sodium-β"-alumina interface capable of achieving high current densities in an electrochemical cell with low interfacial resistance includes the steps of: (a) providing a precursor electrolyte having a resistive surface region, the precursor electrolyte comprising sodium-β"-alumina; (b) removing at least a portion of the resistive surface region; (c) heating the precursor electrolyte to form a solid electrolyte; and (d) contacting a side of the solid electrolyte with a sodium anode.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to U.S. Patent Application No. 16 / 560,229, filed September 4, 2019.

[0002] STATEMENT REGARDING FEDERALLY SPONSORED RESEARCH Not applicable.

[0003] The present invention relates to sodium ion conducting solid electrolytes, sodium battery electrodes, and electrochemical devices such as solid-state sodium batteries that include these electrodes and solid electrolytes. [Background technology]

[0004] Na-β″-alumina (NBA) ceramic is a fast sodium ion conductor and is commercially available as an electrolyte in high temperature sodium nickel chloride (NaNiCl) and sodium-sulfur (NaS) batteries.

[0005] Currently, electric vehicles are powered using lithium-ion battery technology. However, they are not yet competitive with conventional fuel vehicles and suffer from safety concerns related to the use of flammable liquid electrolytes. Ceramic solid electrolytes are non-flammable and therefore can provide a safe alternative to conventional liquid electrolytes. Moreover, the use of metallic anodes can allow for a significant increase in energy density.

[0006] One challenge in the development of sodium solid-state batteries is associated with the high interfacial resistance between the ceramic NBA electrolyte and the metallic sodium anode. This high interfacial resistance has been shown to significantly reduce the critical current density that the cell can withstand before shorting the cell by the formation of metallic filaments through the electrolyte, called dendrites. The cause of the high interfacial resistance has not yet been established, but it is believed that insufficient wetting of the sodium and the presence of impurities at the surface of the NBA formed by exposure to moisture and air play a role. Various strategies have been developed, such as coating the NBA surface with lead, carbon or tin, or heat treating the NBA at 400 °C before cell assembly. Although these results have been shown to be successful in improving sodium wetting, recent reports still present large interfacial resistances of several hundred Ω at room temperature.

[0007] The reduction of the interfacial resistance is currently also being intensively investigated for Li-ion conducting ceramics, in particular lithium lanthanum zirconium oxide (LLZO) ceramics. It was shown that heat treatment of LLZO ceramics was successful in reducing the interfacial resistance by removing surface impurities. Despite the low interfacial resistance, at room temperature (1 mA / cm 2 ) is still below the minimum required for fast charging applications such as electric vehicles (>3mA / cm 2 ). The critical current density refers to the current density that a solid electrolyte can support before failure is observed. Summary of the Invention [Problem to be solved by the invention]

[0008] Therefore, there is a need for methods to reduce the interfacial resistance between the electrodes and the solid electrolyte and to increase the critical current density of solid-state batteries. [Means for solving the problem]

[0009] The present disclosure provides methods for forming and processing electrochemical devices to reduce the area specific resistance (ASR) of the interfacial resistance between a solid electrolyte material and an electrode in an electrochemical device. In one non-limiting embodiment, a method for reducing the interfacial resistance between metallic sodium and a sodium-β″-alumina electrolyte is disclosed. The technique involves polishing the surface of the sodium-β″-alumina ceramic, followed by heat treatment in an inert atmosphere. In a second step, metallic sodium is placed on the sodium-β″-alumina ceramic and stack pressure is applied to enhance adhesion of the sodium to the ceramic electrolyte. This technique for forming a sodium / sodium-β″-alumina interface has been shown to provide a resistance of <10 Ω cm at room temperature. 2 and <3Ωcm at 60℃ 2 and 12 mA / cm 2 and 18mA / cm 2 This demonstrates the ability to use solid sodium / sodium-β″-alumina interfaces without surface modification or interfacial layers in next-generation solid-state sodium-based batteries.

[0010] In one aspect, the present disclosure provides a method of forming a solid electrolyte. The method may include (a) providing a precursor electrolyte having a resistive surface region, the precursor electrolyte comprising metal cation-alumina; (b) removing at least a portion of the resistive surface region; and (c) heating the precursor electrolyte to form a solid electrolyte. The metal cation may be selected from the group consisting of cations of alkali metals. The alkali metal may be sodium. The alkali metal may be lithium. The metal cation-alumina may be selected from the group consisting of sodium-β-alumina and sodium-β″-alumina. The metal cation-alumina may be sodium-β″-alumina, and the precursor electrolyte further comprises a stabilizer for the sodium-β″-alumina. The stabilizer may be selected from the group consisting of Li2O, MgO, NiO, CoO, ZnO, and mixtures thereof.

[0011] In this method, step (a) can include combining a first solid comprising aluminum, a second solid comprising sodium, and a third solid comprising lithium to form a mixture, and sintering the mixture to form a precursor electrolyte. In this method, step (b) can include removing a portion of the resistive surface region with an abrasive particle. In this method, step (c) can include heating the precursor electrolyte at a temperature in the range of 400° C. to 1600° C. In this method, step (c) can include heating the precursor electrolyte at the temperature for 0.1 seconds to 5 hours. In this method, step (c) can include heating the precursor electrolyte in an inert atmosphere.

[0012] In another aspect, the disclosure provides a method for forming an electrochemical device. The method may include (a) providing a precursor electrolyte having a resistive surface region, the precursor electrolyte comprising metal cation-alumina; (b) removing at least a portion of the resistive surface region; (c) heating the precursor electrolyte to form a solid electrolyte; and (d) contacting a side of the solid electrolyte with an electrode to form an electrochemical device. In the method, step (d) may further include pressing the solid electrolyte and the electrode together using a force in the range of 0.01 MPa to 10 MPa. The electrode may comprise sodium metal, and the metal cation-alumina may be sodium-β″-alumina. The area specific resistivity between the electrode and the solid electrolyte may be greater than 100 Ω cm. 2 The method may further include contacting the opposite side of the solid electrolyte with a second electrode to form an electrochemical cell. The critical current density of the electrochemical cell at room temperature may be less than 2 mA / cm. 2 It can be made larger.

[0013] The electrode can be an anode consisting essentially of a metal selected from the group consisting of sodium, lithium, potassium, calcium, magnesium, zinc, nickel, aluminum, barium, and strontium. The metal can be sodium. The second electrode can be a cathode comprising an active material selected from the group consisting of layered metal oxides, metal halides, polyanionic compounds, porous carbon, and sulfur-containing materials. The electrode can be an anode comprising a cationic host material. The electrode can be an anode comprising a sodium host material, which can be selected from the group consisting of (i) sodium-doped silicon, germanium, tin, lead, antimony, bismuth, zinc, aluminum, titanium, cobalt, nickel, manganese, cadmium, and mixtures thereof, (ii) sodium-containing alloys of silicon, germanium, tin, lead, antimony, bismuth, zinc, aluminum, titanium, cobalt, nickel, manganese, cadmium, and mixtures thereof, (iii) sodium-containing oxides, carbides, nitrides, sulfides, phosphides, selenides, tellurides, and mixtures thereof, and (iv) carbon. The second electrode can be a cathode comprising an active material selected from the group consisting of layered metal oxides, metal halides, polyanionic compounds, porous carbon, and sulfur-containing materials.

[0014] In another aspect, the present disclosure provides an electrochemical device comprising a solid electrolyte comprising metal cation-alumina and an electrode in contact with a side of the solid electrolyte, the area specific resistance between the electrode and the solid electrolyte being less than 10 Ω cm at room temperature. 2 The electrode may include sodium metal and the metal cation-alumina may be sodium-β″-alumina. The electrochemical device may further include a second electrode in contact with an opposite side of the solid electrolyte, thereby forming an electrochemical cell. The critical current density of the electrochemical cell at room temperature is preferably less than 2 mA / cm. 2 Greater than.

[0015] The electrode can be an anode consisting essentially of a metal selected from the group consisting of sodium, lithium, potassium, calcium, magnesium, zinc, nickel, aluminum, barium, and strontium. The metal can be sodium. The second electrode can be a cathode comprising an active material selected from the group consisting of layered metal oxides, metal halides, polyanionic compounds, porous carbon, and sulfur-containing materials. The electrode can be an anode comprising a cationic host material. The electrode can be an anode comprising a sodium host material, which can be selected from the group consisting of (i) sodium-doped silicon, germanium, tin, lead, antimony, bismuth, zinc, aluminum, titanium, cobalt, nickel, manganese, cadmium, and mixtures thereof, (ii) sodium-containing alloys of silicon, germanium, tin, lead, antimony, bismuth, zinc, aluminum, titanium, cobalt, nickel, manganese, cadmium, and mixtures thereof, (iii) sodium-containing oxides, carbides, nitrides, sulfides, phosphides, selenides, tellurides, and mixtures thereof, and (iv) carbon. The second electrode can be a cathode comprising an active material selected from the group consisting of layered metal oxides, metal halides, polyanionic compounds, porous carbon, and sulfur-containing materials.

[0016] The foregoing and other aspects and advantages of the present invention will become apparent from the following description, in which reference is made to the accompanying drawings, which form a part hereof, and in which is shown by way of illustration one exemplary embodiment of the invention. However, such an embodiment does not necessarily represent the full scope of the invention, and therefore reference should be made to the claims and this specification for interpreting the scope of the invention. [Brief description of the drawings]

[0017] [Figure 1] FIG. 1 is a schematic diagram of a sodium metal battery. [Diagram 2]FIG. 14 shows the effect of heat treatment (HT) temperature on the interfacial resistance. (a) Representative Nyquist plots for different heat treatment temperatures, where the markers represent experimental data and the lines represent fitted data; (b) shows the interfacial resistance as a function of heat treatment temperature; and (c) is a schematic of a symmetric Na / Na-β″-alumina / Na cell and an equivalent circuit for fitting the impedance spectra. [Figure 3-1] FIG. 1 shows XPS peaks of C 1s, O 1s, and Al 2p-Na 2s core levels of Na-β'-alumina before heat treatment (a) to (c), after heat treatment at 400°C (d) to (f), at 700°C (i) to (k), and at 900°C (l) to (n) in an Ar atmosphere. [Figure 3-2] FIG. 1 shows a summary of the surface chemical composition as estimated by XPS for all Na-β′-alumina samples. [Figure 4] FIG. 1 shows (a) a representative Nyquist plot as a function of temperature, (b) temperature dependent interfacial resistance and ionic conductivity, (c) electronic conductivity, and (d) ionic transport number t plotted as 1-t for readability. [Diagram 5] (a) shows a typical potential response of a Na / NBA / Na cell subjected to CCD measurements at room temperature and charged with 0.25 mAh / cm2 per half cycle; (b) shows Nyquist plots before and after short circuit; (c) shows a detailed view of the potential response during CCD measurements at low current density; (d) shows a detailed view of the potential response during CCD measurements at moderate current density; and (e) shows a detailed view of the potential response during CCD measurements near short circuit, showing increased polarization. [Figure 6](a) and (b) show typical potential responses of a Na / NBA / Na cell with CCD measurements at total transferred charge per half cycle Q = 0.25 mAh / cm2 (a) and Q = 3 mAh / cm2 (b) (the potential response for the last two cycles before failure reaches a limit of 4.5 V, but the maximum value of the y-axis scale bar is 1 V for better readability), where a larger amount of total transferred charge leads to higher polarization and premature shorting, and (c) shows the CCD as a function of interface resistance. [Figure 7] The temperature dependence of the CCD and a comparison with the literature are shown in (a) as an Arrhenius equation and (b) as a function of the homologous temperature (T / Tmelting).

[22] is LC De Jonghe, L. Feldman, A. Buechele, Failure modes of Na-beta alumina, “Solid State Ionics, 5” (1981) 267-269, and

[25] is M. Wang, JB Wolfenstine, J. Sakamoto, “Temperature dependent flux balance of the Li / Li7La3Zr2O12 interface”, Electrochim. Acta. 296 (2019) 842-847.

[0018] The present invention will be better understood, and other features, aspects and advantages will become apparent, upon consideration of the following detailed description, which refers to the claims and the drawings. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] Before describing any embodiment of the invention in detail, it should be understood that the invention is not limited in its application to the details of construction and the arrangement of components set forth in the following description or illustrated in the following drawings. The invention is capable of other embodiments and of being practiced or carried out in various ways. It is also to be understood that the phraseology and terminology used herein are for the purpose of description and should not be regarded as limiting. The use of "including," "comprising," or "having" and variations thereof herein means to encompass the items listed thereafter and equivalents thereof as well as additional items.

[0020] The following description is presented to enable those skilled in the art to make and use embodiments of the present invention. Various modifications to the illustrated embodiments will be readily apparent to those skilled in the art, and the general principles of the present specification can be applied to other embodiments and applications without departing from the embodiments of the present invention. Thus, the embodiments of the present invention are not intended to be limited to the embodiments shown, but should be accorded the widest scope consistent with the principles and features disclosed herein. Those skilled in the art will recognize that the examples provided herein have many useful alternatives and are within the scope of the embodiments of the present invention.

[0021] Various embodiments described herein provide methods for forming an interface between a solid electrolyte and a sodium metal anode.

[0022] As used herein, the term "critical current density (CCD)" may refer to the current density at which a solid electrolyte can develop before failure is observed.

[0023] As used herein, the term "area specific resistance (ASR)" can refer to the area specific resistance of any component, but is generally used to define the resistance between the metal anode and the solid electrolyte interface.

[0024] An embodiment described herein relates to a method for reducing ASR at the interface between a solid electrolyte and an anode by removing resistive species. In one non-limiting exemplary application, the solid electrolyte 116 can be used in a sodium metal battery 110 as shown in FIG. 1. The sodium metal battery 110 includes a current collector 112 (e.g., aluminum) in contact with a cathode 114. The solid electrolyte 116 is disposed between the cathode 114 and an anode 118, which in turn is in contact with a current collector 122 (e.g., aluminum). The current collectors 112 and 122 of the sodium-ion battery 10 can be in electrical communication with an electrical component 124. The electrical component 124 can be in electrical communication with the sodium metal battery 110, either with an electrical load that discharges the battery or with a charger that charges the battery. The sodium metal battery 110 can be operated at room temperature.

[0025] The first current collector 112 and the second current collector 122 may comprise a conductive metal or any suitable conductive material. In some embodiments, the first current collector 112 and the second current collector 122 comprise aluminum, nickel, copper, combinations and alloys thereof. In other embodiments, the first current collector 112 and the second current collector 122 have a thickness of 0.1 microns or greater. It should be understood that the thicknesses shown in FIG. 1 are not drawn to scale and that the thicknesses of the first current collector 112 and the second current collector 122 may vary.

[0026] Suitable active materials for the cathode 114 of the sodium metal battery 110 are sodium host materials capable of storing and subsequently releasing sodium ions. Non-limiting exemplary cathode active materials may be selected from the group consisting of layered metal oxides, metal halides, polyanionic compounds, porous carbon, and sulfur-containing materials. Examples of layered metal oxides include NaFeO, NaMnO, NaTiO, NaNiO, NaCrO, NaCoO, and NaVO. Exemplary metal halide compounds have the formula MX mwhere M can be selected from nickel, iron, copper, zinc, cadmium, titanium, aluminum, and tin, X can be selected from iodine, bromine, chlorine, and fluorine, and m corresponds to the valence of the metal M. Non-limiting examples of polyanionic compounds include Na3V2(PO4)3, Na2Fe2(SO4)3, NaFePO4, NaFeP2O7, Na2MP2O7 (where M is at least one of Fe, Ni, Co, and Mn), and Na4M3(PO4)2P2O7 (where M is at least one of Fe, Ni, Co, and Mn). Porous carbon is suitable for sodium-air batteries, and sulfur-containing materials are suitable for sodium-sulfur batteries. The cathode active material can be a mixture of any number of these cathode active materials.

[0027] In some embodiments, the anode 118 of the sodium metal battery 110 consists of sodium metal. In other embodiments, an exemplary anode 118 material consists essentially of sodium metal.

[0028] In an alternative embodiment, the anode comprises a sodium host material selected from the group consisting of: (i) sodium-doped silicon, germanium, tin, lead, antimony, bismuth, zinc, aluminum, titanium, cobalt, nickel, manganese, cadmium, and mixtures thereof, (ii) sodium-containing alloys of silicon, germanium, tin, lead, antimony, bismuth, zinc, aluminum, titanium, cobalt, nickel, manganese, cadmium, and mixtures thereof, (iii) sodium-containing oxides, carbides, nitrides, sulfides, phosphides, selenides, tellurides, and mixtures thereof, and (iv) carbon. The anode can be a mixture of any number of these sodium host materials.

[0029] The electrolyte 116 of the sodium metal battery 110 may be a solid electrolyte material comprising metal cation-alumina, preferably metal cation-β-alumina and metal cation-β″-alumina. The metal cation may be selected from the group consisting of cations of alkali metals. The metal cation is preferably sodium. The metal cation-alumina may be sodium-β-alumina and sodium-β″-alumina. Preferably, the solid electrolyte material comprises sodium-β″-alumina. The solid electrolyte material may further comprise a stabilizer for the sodium-β″-alumina. The stabilizing amount of the stabilizer may be selected from the group consisting of Li2O, MgO, NiO, CoO, ZnO, and mixtures thereof.

[0030] In another non-limiting exemplary application, the solid electrolyte can be used in a lithium metal battery. A suitable active material for the cathode of a lithium metal battery is a lithium host material that can store and subsequently release lithium ions. One exemplary cathode active material is a lithium metal oxide, where the metal is one or more of aluminum, cobalt, iron, manganese, nickel, and vanadium. Non-limiting examples of lithium metal oxides include LiCoO2 (LCO), LiFeO2, LiMnO2 (LMO), LiMn2O4, LiNiO2 (LNO), LiNi x Co y O2, LiMn x Co y O2, LiMn x Ni y O2, LiMn x Ni y O4, LiNi x Co y Al z O2, LiNi 1 / 3 Mn 1 / 3 Co 1 / 3O2, etc. Another example of a cathode active material is a lithium-containing phosphate having the general formula LiMPO4 (where M is one or more of cobalt, iron, manganese, and nickel), such as lithium iron phosphate (LFP) and lithium iron fluorophosphate. Many different elements, such as Co, Mn, Ni, Cr, Al, or Li, can be substituted or added to the structure to affect the electronic conductivity, layer ordering, stability against delithiation, and cycling performance of the cathode material. In some embodiments, a suitable active material for the anode of a lithium metal battery consists of lithium metal. In other embodiments, an exemplary anode material consists essentially of lithium metal. In an alternative embodiment, the anode includes a lithium host material, such as graphite.

[0031] In yet another non-limiting exemplary application, the solid electrolyte can be used in an intercalation battery having a cation chemistry other than sodium or lithium. For example, the anode of the battery can consist essentially of a metal selected from the group consisting of potassium, calcium, magnesium, zinc, nickel, aluminum, barium, and strontium. The cathode can include an active material capable of storing and releasing potassium, calcium, magnesium, zinc, nickel, aluminum, barium, strontium, silver, or thallium cations.

[0032] The present disclosure provides a method of forming a solid electrolyte. The method includes the steps of: (a) providing a precursor electrolyte having a resistive surface region, the precursor electrolyte comprising metal cation-alumina, preferably metal cation-β-alumina or metal cation-β″-alumina; (b) removing at least a portion of the resistive surface region; and (c) heating the precursor electrolyte to form a solid electrolyte. One non-limiting example precursor electrolyte can be formed by combining a first solid comprising aluminum (e.g., AlO(OH)), a second solid comprising sodium (e.g., Na2CO3), and a third solid comprising lithium (e.g., LiOH) to form a mixture, and sintering the mixture to form the precursor electrolyte. The portion of the resistive surface region can be removed with an abrasive particle.

[0033] In some embodiments, heating the precursor electrolyte to remove at least a portion of the resistive surface region is carried out at a temperature greater than 180° C., or greater than 200° C., or greater than 250° C., or greater than 300° C., or greater than 350° C., or greater than 400° C., or greater than 450° C., or greater than 500° C., or greater than 550° C., or greater than 600° C., or greater than 650° C., or greater than 700° C., or greater than 750° C., or greater than 800° C., or greater than 850° C., or greater than 900° C., or greater than 950° C., or greater than 1000° C. Preferably, heating the precursor electrolyte is carried out at a temperature in the range of 400° C. to 1600° C. Alternatively, heating of the precursor electrolyte may be carried out at a temperature in the range of 400°C to 1600°C, or 500°C to 1000°C, or 500°C to 1200°C, or 500°C to 1300°C, or 500°C to 1500°C, or 600°C to 1600°C.

[0034] Heating the precursor electrolyte to remove at least a portion of the resistive surface region can be performed for any time and at any pressure, including above atmospheric pressure, at atmospheric pressure, or below atmospheric pressure. Preferably, the precursor electrolyte is heated at the above temperatures for 0.1 seconds to 5 hours, or 1 to 5 hours, or 2 to 4 hours.

[0035] In some embodiments, heating the precursor electrolyte to remove at least a portion of the resistive surface region occurs in ambient air. In other embodiments, heating the precursor electrolyte to remove at least a portion of the resistive surface region occurs in an atmosphere free of the presence of moisture or CO2. In some embodiments, the atmosphere comprises an inert gas. Suitable inert gases include helium, argon, neon, xenon, krypton, radon, and nitrogen.

[0036] In some embodiments, heating the precursor electrolyte to remove at least a portion of the resistive surface area comprises removing 0.1% to 99.9% of the resistive surface area. In some embodiments, heating the precursor electrolyte removes 5% or more, 10% or more, 15% or more, 20% or more, 25% or more, 30% or more, 35% or more, 40% or more, 45% or more, 50% or more, 55% or more, 60% or more, 65% or more, 70% or more, 75% or more, 80% or more, 85% or more, 90% or more, 95% or more of the resistive surface area.

[0037] The present disclosure also provides a method for forming an electrochemical device. The method includes the steps of: (a) providing a precursor electrolyte having a resistive surface region, the precursor electrolyte comprising metal cation-alumina, preferably metal cation-β-alumina or metal cation-β″-alumina; (b) removing at least a portion of the resistive surface region; (c) heating the precursor electrolyte to form a solid electrolyte; and (d) contacting a side of the solid electrolyte with an electrode to form an electrochemical device. Step (d) may further include pressing the solid electrolyte and the electrode together using a force in the range of 0.01 MPa to 10 MPa. In one version of the method, the electrode comprises sodium metal and the metal cation-alumina is sodium-β″-alumina. After contacting a side of the solid electrolyte with the electrode, the area specific resistivity between the electrode and the solid electrolyte is greater than or equal to 200 Ω cm. 2 Less than or equal to 100Ωcm 2 Less than or equal to 75Ωcm 2 Less than or equal to 50Ωcm 2Less than or equal to 25Ωcm 2 Less than or equal to 10Ωcm 2 Less than or equal to 5Ωcm 2 Less than or equal to 3Ωcm 2 Less than or equal to 2Ωcm 2 is less than.

[0038] Before, during, or after formation of the electrochemical device, the opposite side of the solid electrolyte can be contacted with a second electrode to form an electrochemical cell. After the electrochemical cell is formed, the critical current density of the electrochemical cell at room temperature is greater than or equal to 2 mA / cm. 2 or more than 3mA / cm 2 or greater than 4mA / cm 2 or greater than 5mA / cm 2 or greater than 8mA / cm 2 or greater than 10mA / cm 2 or greater than 12mA / cm 2 or greater than 15mA / cm 2 or greater than 20mA / cm 2 It's super.

[0039] <Example> The following examples represent and are provided to further illustrate certain embodiments and aspects of the present invention and should not be construed as limiting the scope of the invention.

[0040] [overview] All-solid-state batteries with alkali metal anodes have the potential to achieve high energy density. However, the onset of dendrite formation limits the maximum plating current density across the solid electrolyte, preventing fast charging. It has been shown that the maximum plating current density is related to the interfacial resistance between the solid electrolyte and the metal anode. Na-β″-alumina ceramic is an excellent candidate as an electrolyte for room-temperature all-solid-state batteries due to its high ionic conductivity, low electronic conductivity, and stability against sodium metal. Herein, we show that heat treatment of Na-β″-alumina ceramic in an argon atmosphere reduces the electrochemical conductivity to <10 Ω cm at room temperature. 2 and 12mA / cm 2The critical current density obtained for Na-β''-alumina is higher than that of garnet-type Li7La3Zr2O under comparable conditions. 12 10 times higher than that measured for the electrolyte. X-ray photoelectron spectroscopy showed that the elimination of hydroxyl groups and carbon contamination at the interface between Na-β''-alumina and sodium metal was important to reach such values. 12 We consider the role of alkali metals in governing the interfacial kinetics by comparing the temperature-dependent stripping / plating behavior of Na-β''-alumina ceramics. This example provides new insights into dendrite formation and paves the way for fast-charging all-solid-state batteries. Specifically, we demonstrate that Na-β''-alumina ceramics can be charged with currents up to 12 mA / cm at room temperature. 2 This paves the way for fast-charging solid-state sodium batteries.

[0041] [Introduction] 10mA / cm at room temperature 2 Enabling reversible stripping and plating of alkali metals at current densities above 10 ...

[0042] Although the underlying mechanism is still under debate, it has been shown that the critical current density (CCD) for dendrite formation is related to the interfacial resistance between the solid electrolyte and the metal anode [6]. For example, in Li7La3Zr2O 12Several strategies have been employed to reduce the interfacial resistance at the interface between the (LLZO) electrolyte and the lithium metal anode. LLZO is currently being intensively studied due to its high ionic conductivity (~1 mS / cm at room temperature) and high stability against lithium metal [Refs. 7, 8]. Strategies include the use of interfacial layers (e.g., Au [Ref. 9], Ge [Ref. 10]), heat treatment to remove surface contamination from the electrolyte [Ref. 6], or promoting contact by pressurizing the cell during cycling [Refs. 11, 12]. Despite obtaining interfacial resistance values ​​comparable to those measured for the interface between liquid electrolyte and lithium metal, the CCD values ​​are still below the fast charging requirements (e.g., 5 mAh / cm charged / discharged at 2C). 2 Equivalent to an area charge capacity of 10mA / cm 2 [References 13]).

[0043] In this example, we investigate Na-β''-alumina ceramics as potential electrolytes for fast-charging solid-state batteries. Na-β''-alumina is already commercially used in high-temperature sodium nickel chloride (NaNiCl) and sodium-sulfur (NaS) batteries operating at around 300 °C due to its high ionic conductivity, low electronic conductivity, and stability towards sodium metal [Refs. 14, 15, 16]. However, high interfacial resistance, possibly associated with poor sodium wetting and the presence of surface impurities, has hindered its use as a solid-state electrolyte for room-temperature batteries [Ref. 16].

[0044] Herein, a low interfacial resistance to sodium metal <10 Ω cm was achieved by applying a heat treatment in an argon atmosphere to a finely polished Na-β″-alumina surface. 2 It can achieve 12mA / cm at room temperature, which meets the fast charging requirements. 2 It is shown that this allows for CCD values ​​of 1000 . The dependence of the CCD value on the total charge transferred is also investigated. Compared to LLZO, a 10-fold increase in current density is observed despite similar transport numbers. The important role of the electronic conductivity of the electrolyte and the melting temperature of the alkali metals on the CCD are also discussed.

[0045] Materials and Methods Spray-dried Li-stabilized Na-β''-alumina powder was prepared by solid-state synthesis from boehmite (AlO(OH)), lithium hydroxide (LiOH), and sodium carbonate (Na2CO3) [Ref. 17]. The powder was pressed into green bodies of 15 mm diameter. These were sintered in static air at 1600 °C for 5 min in a high-temperature laboratory furnace (Carbolite Gero HTF1700) applying constant heating and cooling rates of 3 °C / min. To mitigate sodium (and lithium) losses and promote shrinkage during sintering, the samples were placed on green buffer disks made from the same Na-β''-alumina powder. The samples and buffer disks were packed into dense magnesium spinel domes and corresponding magnesium spinel support disks at 0.14 g / cm. 3 The pellets were then ground plane-parallel with increasingly fine sandpaper and polished with a series of diamond pastes until a final polish using a 0.1 μm diamond paste. The resulting pellets had final dimensions of 1.4 ± 0.3 mm thickness and 12.7 mm diameter. The samples were then heat treated in an argon atmosphere at temperatures between 400 °C and 900 °C for 3 h.

[0046] The cell assembly and electrochemical characterization were carried out under argon atmosphere in a glove box. The heat-treated Na-β''-alumina ceramic was first wrapped around 0.49 cm on both sides using polyimide foil. 2The pellet was masked over an area of ​​100 nm. Mechanically cleaned sodium foil was then pressed onto both sides of the masked pellet at a pressure of 3.4 MPa. Electrochemical characterization was carried out using a Biologic VMP-300 galvanostat / potentiostat using a nickel current collector at a pressure of 3.4 MPa in an argon glove box. The temperature-dependent ionic conductivity of Na-β''-alumina was extracted from potentiostatic electrochemical impedance spectroscopy (PEIS) data measured at frequencies from 0.5 Hz to 7 MHz with a sinusoidal amplitude of 20 mV. The temperature-dependent electronic conductivity was calculated as the ratio of Na / Na + The critical current density (CCD) was determined by DC polarization method applying step potential difference measurements (Mott-Schottky) at 1, 2, and 3 V against the surface of the sample. The critical current density (CCD) was evaluated by constant current measurements applying an initial pressure of 3.4 MPa. ... 2 or 3mAh / cm 2 The current density was increased with each cycle while transferring a constant charge of 0.01 μm. PEIS was performed before and after each plating and stripping cycle. CCD was defined as the current density at which a short circuit of the cell occurred, indicated by a sudden drop in the potential response and cell impedance. CCD values ​​are given as the average over three to four measurements, and error bars represent the maximum and minimum values.

[0047] X-ray photoelectron spectroscopy (XPS) measurements were performed at room temperature on a PHI Quantum2000 using a monochromated Al Kα X-ray source (1484.6 eV) with a pass energy of 30 eV. All measurements were performed on three different areas of each sample, 150 μm in diameter. Charging of the samples was prevented by charge compensation provided by a low-energy electron gun. XPS data were processed with CasaXPS software. The spectra were calibrated by setting the hydrocarbon component of the C 1s photoemission peak to a binding energy of 285.0 eV.

[0048] [Results and Discussion] <Effect of heat treatment temperature on interface resistance and interface chemistry> The interfacial resistance between sodium metal and Na-β''-alumina (R intTo study the effect of heat treatment on the surface tension, potentiostatic electrochemical impedance spectroscopy (PEIS) measurements were performed on Na-β''-alumina pellets heat treated in argon at temperatures between 400 °C and 900 °C and compared with as-polished untreated samples. These measurements were carried out in a symmetric Na / Na-β''-alumina / Na cell shown in Figure 2(c). A mask was applied on the Na-β''-alumina to obtain a clear contact area between the Na-β''-alumina and the Na disk, and a pressure of 3.4 MPa was applied during the PEIS measurements. Representative Nyquist plots for the various heat treatment conditions are shown in Figure 2(a). The PEIS spectrum shows a peak density of 4.3 × 10 5 The results reveal two semicircles representing the impedance contributions from the Na-β''-alumina ceramic, characterized by a vertex frequency of 100 Hz, and from the Na / Na-β''-alumina interface, characterized by vertex frequencies ranging from 10 to 400 Hz. While the Na-β''-alumina contribution remains constant, the interfacial contribution decreases dramatically with increasing heat treatment temperature. To quantify the change in the interfacial resistance with heat treatment temperature, the PEIS spectra are analyzed using an additional resistivity (R uc ) to account for any uncompensated resistance, for example from the cell casing and electrical connections (see FIG. 2(c)). The interface resistance was normalized by the mask area and divided by two for the two interfaces measured. The results of the fits are shown in Table 1 and FIG. 2(b) on a semi-log scale as a function of heat treatment temperature. Tens of thousands of Ω cm for the non-heat treated sample. 2 to 8Ωcm 2 A significant reduction in the interfacial resistance to sodium metal is achieved by heat treating Na-β''-alumina pellets at 900 °C, while the CPE value increases by two orders of magnitude. Thus, heat treating Na-β''-alumina ceramics in an argon atmosphere is a very effective method for reducing the interfacial resistance to sodium metal. [Table 1]

[0049] To investigate the effect of heat treatment on the Na-β″-alumina electrolyte surface, we performed XPS on Na-β″-alumina pellets before and after heat treatment at 400°C, 700°C and 900°C. The C 1s, O 1s, Al 2p and Na 2s core level spectra are shown in Figure 3-1. The results are summarized in Figure 3-2. The main peak in the C 1s spectrum at 285.0 eV (by calibration) is due to adventitious carbon species (CC / CH). Carbon oxide contamination (CO and OC=O) is detected at higher binding energies. Only small amounts (<1 at.%) of NaCO3 were detected on the surface above 289 eV before and after the 400°C heat treatment and were no longer detected after the higher temperature heat treatment.

[0050] The O 1s peak of untreated Na-β''-alumina is very broad and cannot be fitted by a single component. The width of this peak decreases significantly with increasing heat treatment temperature with the formation of a small shoulder on the high bond energy side. According to Kloprogge et al., “XPS study of the major minerals in bauxite: Gibbsite, bayerite and (pseudo-)boehmite”, Journal of Colloid and Interface Science, Volume 296, Issue 2, April 15, 2006, pages 572-576, we choose to take two main components to fit this peak, which represent oxygen (Al-O, about 530.9 eV) in the crystal structure and hydroxyl (Al-OH, 532.5 eV) groups present on the surface. In addition, oxygen atoms bonded to carbon (CO, OC=O, NaCO3) are taken into account in the ratio determined from the C 1s peak, corrected for the respective photoelectron cross sections and chemical formulas. Interestingly, the area of ​​the Al-OH components is comparable to that of the Al-O components, but is significantly reduced after heat treatment at 900 °C. This is strong evidence that reducing the amount of interfacial hydroxyl groups is important for obtaining low ionic interfacial resistance to sodium metal.

[0051] For completeness, the Al 2p and Na 2s spectra are also shown in Fig. 3. Following Kloprogge et al. and Zahr et al., “Characterisation of oxide and hydroxide layers on technical aluminum materials using XPS”, Vacuum, Volume 86, Issue 9, March 14, 2012, pp. 1216-1219, we refrain from deconvoluting the Al 2p doublet into Al-O and Al-OH components with different binding energies, and the peak area ratio between the components is constrained to the value calculated from the analysis of the O 1s peak. It should be noted that the presence of the Al 2p peak confirms that the surface contamination layer is thinner than the photoelectron inelastic mean free path.

[0052] 《Temperature-dependent transport properties》 To better understand the transport kinetics at the Na / Na-β''-alumina interface, we analyze the different conduction processes as a function of temperature. Plot (a) in Fig. 4 exemplarily shows the Nyquist plot of a Na / Na-β''-alumina / Na cell measured between 0 °C and 60 °C. It is clear that the impedance of both the Na-β''-alumina ceramic and the interface decreases with increasing temperature. Extracting both contributions using the equivalent circuit in Fig. 2(c) gives the temperature-dependent ionic conductivity and interface resistance shown in Fig. 4(b). The ionic conductivity of the Na-β''-alumina ceramic at room temperature is 1.3 mS / cm and is expressed as ln(σ ion T) versus 1000 / T. In comparison, the interfacial process follows Arrhenius behavior with an activation energy of 0.35 eV derived from a linear fit of ln(T / R int) versus 1000 / T, indicating that the charge transfer process is not hindered at the interface. Since pressure is applied during the measurements, good contact is expected to be maintained even at low temperatures. We therefore attribute the temperature-dependent interfacial resistance to improved kinetics rather than to a change in the viscosity of sodium metal with temperature. An additional requirement for a solid electrolyte is a low electronic conductivity σ el and a high ionic transport number, t. In Fig. 4(c) and (d), the electronic conductivity and ionic transport number, t, are shown from 0 to 60 °C and plotted as 1-t for better readability. At room temperature, it is 6.4 × 10 -11 A low electronic conductivity of 0.2 S / cm is measured, which increases only slightly with temperature according to Arrhenius behavior with an activation energy of 0.84 eV. In this temperature range, the corresponding transport number is close to 1. Compared with recently published data on the electronic conductivity of Na-β''-alumina [Ref. 18], the room temperature electronic conductivity value measured here is 10 times smaller. This difference can be attributed to the variations in microstructure and phase content, but the stabilization time during DC polarization and the use of two blocking electrodes versus the Hebb Wagner technique with metal electrodes may also play a role. Overall, the interfacial charge transfer process with high ionic conductivity and low resistivity coupled with the low electronic conductivity of Na-β''-alumina ceramics are important facilitators for the development of solid-state Na / Na-β''-alumina batteries.

[0053] Charge and R int Critical current density in sodium-β''-alumina ceramics as a function of temperature. After demonstrating low interfacial resistance and favorable charge transport properties, we now turn our attention to the sodium stripping / plating behavior in a symmetric Na / Na-β″-alumina / Na cell. The critical current density (CCD) at which dendrites propagate through the Na-β″-alumina ceramic was determined by galvanostatic measurements. To ensure good contact between sodium metal and the Na-β″-alumina ceramic, a current of 10 μA / cm was used. 2Ten cycles of 1 h were first applied at a current density of 0.05 mAh / cm2 [Ref. 19], followed by a current density of 0.25 mAh / cm2, which is comparable to recent work on LLZO. 2 CCD measurements were performed while transferring a constant charge density of 1000 mA / cm, with increasing current density at each cycle. The cell was placed under a pressure of 3.4 MPa to mitigate the formation of voids in the sodium metal during stripping, as recently demonstrated for lithium metal in contact with LLZO [Refs. 11, 12]. After the measurement, the pressure was recorded to still be about -5% of its initial value. The potential response during a standard CCD measurement is shown in Figure 5(a) for a sample heat-treated at 900 °C. In this example, the CCD measured a current of 9 mA / cm, as observed by the sudden drop in potential to 0 V. 2(see arrow in Fig. 5e), indicating a short circuit of the cell due to dendrite formation. In some cases, if the dendrites short the cell locally only at the point contacts, the potential may partially recover as shown in the example in Fig. 5e. To confirm the short circuit of the cell, PEIS was performed between each stripping / plating cycle. In Fig. 5b, a standard PEIS spectrum is shown before and after reaching the CCD. Under the CCD, the spectrum is dominated by the electrolyte contribution (as explained by the parallel connection of RNBA and CPENBA in Fig. 2c). After the short circuit, the electrolyte contribution is significantly reduced and the spectrum is dominated by a resistive behavior with some stray inductance and a small capacitance contribution, which is probably related to the local point contacts of the sodium dendrites. A more detailed look at the potential response at different stages of the measurement (box in Fig. 5a) is shown in Fig. 5c, d, and e. At low current densities, the potential response follows an ohmic behavior, U=RI. where U is the potential, R is the total cell resistance, and I is the current observed by the stable potential. The overpotential at low current densities is given only by the electrolyte, since the interfacial resistance is negligible. As the current density increases, the potential response deviates from ohmic behavior until the CCD is reached. The increase in potential has recently been attributed entirely to void formation in the lithium metal at the interface with LLZO during stripping

[12] , but confirmation of the void formation result from stripping requires measurements with a reference electrode.

[0054] Here, we investigate the effect of charge density and interface resistance on the CCD. In Fig. 6(a) and (b), we see that the charge density is 0.25 mAh / cm 2 and 3mAh / cm 2 At a charge density of 6.6mA / cm 2 A comparison of the potential response of cells cycled up to a current density of 0.25 mAh / cm is shown. 2 The cell cycled at a charge density of 6.6 mA / cm 2 No breakdown occurs up to 3mAh / cm 2The cell cycled with a charge of 5.5 mA / cm2 had a current of 5.5 mA / cm2, as observed by the sudden drop in the potential response to 0 V, indicated by the arrow in Figure 6(b). 2 The cells fail at 0.25 V. Compared to the potential response of cells cycled at low charge densities, the polarization of cells cycled at high charge densities increases continuously with increasing current density until a cutoff voltage of 4.5 V is reached (axis cut at 1 V for better readability). We attribute this deviation from ohmic behavior to void formation in sodium metal near the interface with Na-β''-alumina caused by long stripping cycles, when a larger amount of charge is transferred per cycle. The resulting voids formed at the interface reduce the contact surface area and thus increase the interfacial resistance. Thus, a higher overpotential is required to deliver a constant current. Although a reference electrode would likely be required to decouple stripping from plating effects, the premature cell failure with increased charge supports the void formation hypothesis. Although void formation can be avoided by increasing the pressure [Refs. 11, 12], we recommend a pressure of 0.25 mAh / cm to minimize void formation. 2 All CCD measurements were performed at a charge density of 0.01μm.

[0055] The effect of increasing the heat treatment (HT) temperature is shown in Figure 6c. The CCD value increases significantly with decreasing interfacial resistance. As previously reported in [Ref. 6], this effect is due to the suppression of localized regions characterized by higher current densities, often called "hot spots", which prematurely reach the CCD value. This observation was also made for Na-β''-alumina using a molten sodium metal anode, which allowed for higher charges to be passed in cells characterized by lower charge transfer resistance [Ref. 20]. For the maximum applied heat treatment temperature, 12 mA / cm 2The average CCD value over four samples is obtained. To the best of our knowledge, this is the highest CCD value reported for a solid electrolyte at room temperature (without implementing a porous electrolyte layer that locally reduces the current density by increasing the surface area as in [Ref. 21]). Note that the maximum heat treatment temperature was limited to 900 °C by the furnace. Higher temperatures could further reduce the interfacial resistance and thus increase the CCD value, but void formation at the interface could limit the physical maximum CCD. Nevertheless, this surface treatment gives optimistic results for the implementation of fast-charging solid-state batteries.

[0056] <Comparison of temperature-dependent CCD and literature> The effect of stripping / plating temperature on the CCD was investigated for samples heat treated at 900°C in the temperature range from 0 to 60°C. The results are plotted in the Arrhenius representation in Figure 7(a). Similar to the literature, an exponential relationship is found between CCD and inverse temperature (taking into account the error bars) with an activation energy of 0.27 eV. Increasing the temperature to 60°C reduces the CCD to 19 mA / cm 2 Critical current densities up to 10 mA / cm can be achieved, which is consistent with acoustic measurements from the 1980s using liquid sodium mercury amalgam [Ref. 22]. Although this temperature behavior is not currently fully understood, Han et al. recently proposed that dendrite formation is governed by the electronic conductivity of the electrolyte, which in turn governs the rate at which sodium ions are reduced to metallic sodium in the bulk of the solid electrolyte above the plating potential [Ref. 23]. They found that 2 To allow dendrite-free plating at 10 -12 It was concluded that the saturation voltage should be less than 6×10 S / cm. This criterion is based on the measurements at room temperature in this example (6×10 -11 S / cm, 12mA / cm 2 ), but the electronic conductivity at 60°C is three orders of magnitude (2×10 -9 The critical current density is improved by 30%, while the critical current density is shifted by 10 S / cm. Furthermore, Na-β''-alumina has an electronic conductivity of about 10 -8S / cm [Reference 24] at 350 °C, up to 300 mA / cm 2 It was also shown that the critical current density of [Ref. 22] can be maintained at 1000 K. It is clear that the ionic conductivity and charge transfer kinetics are also improved simultaneously, and therefore a theory based only on electronic conductivity cannot fully explain the temperature-dependent CCD measurements. Some of the inventors have recently hypothesized that the properties of the alkali metal electrode may govern the dendrite formation [Ref. 25]. It has been reported that flux imbalance at the interface caused by the difference between the metal self-diffusivity in the alkali metal and the ionic diffusivity in the electrolyte may give rise to metal pile-ups at the interface, which may eventually act as nucleation sites for dendritic growth. To better understand the role of the electrode metal, we compare in Fig. 7(a) the results of LLZO obtained in our previous work [Ref. 25]. It should be noted that identical measurement conditions were applied and similar interfacial resistances were obtained. Over the measured temperature range, the CCD values ​​of Na-β''-alumina are systematically 10 times higher than those for LLZO. It is interesting to note that the error bars for Na-β''-alumina are also larger. On the one hand, this could be a consequence of the bimodal grain and pore size distribution of Na-β″-alumina ceramics as recently described in detail in ref. 26. In particular, the interfacial pores could result in an increase in the local current density. On the other hand, this could be a consequence of the amplifying effect of surface inhomogeneities at higher current densities, as also observed to a lesser extent for LLZO for increasing temperatures. Due to the difference in melting temperatures (97.79 °C for Na and 180.5 °C for Li), the metals have different viscosities at the same measurement temperature. To take this difference into account, we have calculated the temperature (T) as the melting temperature of the alkali metal (T melting The CCD values ​​are plotted in Figure 7(b) as a function of the homologous temperature, defined as the CCD ratio divided by the homologous temperature (Tc). The results in Figure 7(b) show an exponential relationship for both systems, with a deviation in the behavior for homologous temperatures >0.66 (corresponding to >0 °C for the Na system and >60 °C for the Li system). These differences can be explained by differences in the flux balance at the electrolyte / electrode interface, i.e., in the lithium system, the amount of Li in Li is much greater than in the Li system. 0 and Li in LLZO +The diffusion rates of -11 cm 2 / s vs. 2 × 10 -9 cm 2 / s). In comparison, Na in Na 0 and Na in Na-β''-alumina + The diffusivities of the ions differ by only a factor of about 10 (5 × 10 -9 vs 3×10 -8 cm 2 / s). Thus, the plated Na atoms migrate more readily into the bulk of the metal than the Li atoms, allowing the use of higher current densities up to the point when the flux of ions migrating from the electrolyte to the interface is higher than the flux of metal atoms migrating from the interface into the bulk. Furthermore, it is interesting to note that the self-diffusivity of sodium is about 100 times that of lithium (5×10 and 5×10 respectively at room temperature). -9 cm 2 / s vs 5×10 -11 cm 2 / s). It is therefore expected that higher stripping rates can be applied with the sodium metal anode up to the point where the vacancies become supersaturated and start to form voids at the interface (assuming that the self-diffusivity is proportional to the vacancy diffusion). Similarly, the void-filling process during plating is also expected to be faster due to the higher self-diffusivity, allowing for higher current densities to replenish the surface. However, modeling the situation at the interface can be beneficial to fully understand the mechanism of dendritic growth, taking into account the mechanical properties of the alkali metals, such as creep, elasticity, and plastic properties.

[0057] [Conclusion] When finely polished Na-β''-alumina ceramics were heat-treated in an argon atmosphere to remove surface hydroxyl groups, the interfacial resistance of a symmetric Na / Na-β''-alumina cell was reduced to Ωcm at 100 s at room temperature. 2 to 8Ωcm 2 This improvement in interfacial resistance was 0.25 mAh / cm per half cycle. 2 The critical current density for a total mobile charge density of 0.3 to 12 mA / cm 2The temperature-dependent critical current density measurements both show exponential behavior with comparable activation energies, although not intending to be bound by theory, we attribute the 10-fold difference in the CCD to the diffusion properties of the alkali metal and solid electrolyte.

[0058] Currently, the development of all-solid-state batteries based on sodium metal anodes is hindered by the lack of availability of suitable sodium cathode materials that can compete in performance with, for example, nickel-rich layered oxides (e.g., NMC811) used in lithium-ion batteries. However, our results show that the use of such suitable sodium cathode materials that can compete in performance makes all-solid-state sodium metal batteries with fast charging capability based on Na-β″-alumina electrolyte a very promising option for rapid commercialization and market deployment.

[0059] Overall, it has been demonstrated that the combination of fine grinding and heat treatment temperature processes in an inert atmosphere makes it possible to obtain low interfacial resistance and unprecedented high critical current density in contact with metallic Na. These results are promising for the development of fast-charging all-solid-state batteries.

[0060] Therefore, Na-β″-alumina (NBA) ceramics are excellent candidates for use as electrolytes in room-temperature solid-state batteries due to their high ionic conductivity, low electronic conductivity, and stability against metallic sodium. One of the challenges associated with the fabrication of solid-state batteries is the high solid-solid interfacial resistance between metallic sodium and the ceramic electrolyte, which reduces the critical current density. The present example describes the surface treatment of NBA ceramics, as well as the fabrication of NBA ceramics with a resistivity of <10 Ω cm at room temperature. 2 and 12mA / cm 2This is a great way to get the Na / NBA sports competition.

[0061] <Specific Condition> [1]D. Lin , Y. Liu , Y. Cui , Reviving the lithium metal anode for high-energy batteries , Nat. Nanotechnol. 12 (2017) 194–2 doi:10.1038 / nano.2017.16 [2]Y. Ren, Y. Shen, Y. Lin, C.-W. Nan, Direct observation of lithium dendrites inside a garnet-type lithium-ion solid electrolyte, Electrochem. Commun. 57 (2015) 27–30. doi:10.1016 / j.elecom.2015.05.001 [3]EJ Cheng, A. Sharafi, J. Sakamoto, Intergranular Li metal propagation through polycrystalline Li 6.25 Al 0.25 La3Zr2O 12 ceramic electrolyte, Electrochem. Acta. 223 (2017) 85–91. doi:10.1016 / electact.2016.12.018 [4]L. Porz , T. Swamy , BW Sheldon , D. Rettenwander , T. Froemling , HL Thaman , S. Berendts , R. Uecker , WC Carter , Y.-M. Chiang, Mechanism of Lithium Metal Penetration through Inorganic Solid Electrolytes, Adv. Energy Mater. 7 (2017) 1701003. doi:10.1002 / aenm.201701003 [5]A. Gupta, E. Kazyak, N. Craig, J. Christensen, N.P. Dasgupta, J. Sakamoto, Evaluating the Effects of Temperature and Pressure on Li / PEO-LiTFSI Interfacial Stability and Kinetics, J. Electrochem. Soc. 165 (2018) A2801-A2806. doi:10.1149 / 2.0901811jes [6]A. Sharafi, E. Kazyak, A.L. Davis, S. Yu, T. Thompson, D.J. Siegel, N.P. Dasgupta, J. Sakamoto, Surface Chemistry Mechanism of Ultra-Low Interfacial Resistance in the Solid-State Electrolyte Li7La3Zr2O 12 , Chem. Mater. 29 (2017) 7961-7968. doi:10.1021 / acs.chemmater.7b03002 [7]R. Murugan, V. Thangadurai, W. Weppner, Fast Lithium Ion Conduction in Garnet-Type Li7La3Zr2O 12 , Angew. Chemie Int. Ed. 46 (2007) 7778-7781. doi:10.1002 / anie.200701144 [8]V. Thangadurai, S. Narayanan, D. Pinzaru, Garnet-type solid-state fast Li ion conductors for Li batteries: critical review, Chem. Soc. Rev. 43 (2014) 4714. doi:10.1039 / c4cs00020j [9]C.-L. Tsai, V. Roddatis, C.V. Chandran, Q. Ma, S. Uhlenbruck, M. Bram, P. Heitjans, O. Guillon, Li7La3Zr2O 12 Interface Modification for Li Dendrite Prevention, ACS Appl. Mater. Interfaces. 8 (2016) 10617-10626. doi:10.1021 / acsami.6b00831

[10] W. Luo, Y. Gong, Y. Zhu, Y. Li, Y. Yao, Y. Zhang, K.K. Fu, G. Pastel, C.-F. Lin, Y. Mo, E.D. Wachsman, L. Hu, Reducing Interfacial Resistance between Garnet-Structured Solid-State Electrolyte and Li-Metal Anode by a Germanium Layer, Adv. Mater. 29 (2017) 1606042. doi:10.1002 / adma.201606042

[11] T. Krauskopf, H. Hartmann, W.G. Zeier, J. Janek, Toward a Fundamental Understanding of the Lithium Metal Anode in Solid-State Batteries - An Electrochemo-Mechanical Study on the Garnet-Type Solid Electrolyte Li 6.25 Al 0.25 La3Zr2O 12 , ACS Appl. Mater. Interfaces. 11 (2019) 14463-14477. doi:10.1021 / acsami.9b02537

[12] M.J. Wang, R. Choudhury, J. Sakamoto, Characterizing the Li-Solid-Electrolyte Interface Dynamics as a Function of Stack Pressure and Current Density, Joule. (2019) 1-14. doi:10.1016 / j.joule.2019.06.017

[13] P. Albertus, S. Babinec, S. Litzelman, A. Newman, Status and challenges in enabling the lithium metal electrode for high-energy and low-cost rechargeable batteries, Nat. Energy. 3 (2018) 16-21. doi:10.1038 / s41560-017-0047-2

[14] C.-H. Dustmann, Advances in ZEBRA batteries, J. Power Sources. 127 (2004) 85-92. doi:10.1016 / j.jpowsour.2003.09.039

[15] J.L. Sudworth, The sodium / nickel chloride (ZEBRA) battery, J. Power Sources. 100 (2001) 149-163. doi:10.1016 / S0378-7753(01)00891-6.

[16] J.L. Sudworth, The sodium / sulphur battery, J. Power Sources. 11 (1984) 143-154. doi:10.1016 / 0378-7753(84)80080-4

[17] M.-C. Bay, M.V.F. Heinz, R. Figi, C. Schreiner, D. Basso, N. Zanon, U.F. Vogt, C. Battaglia, Impact of Liquid Phase Formation on Microstructure and Conductivity of Li-Stabilized Na-β″-alumina Ceramics, ACS Appl. Energy Mater. 2 (2019) 687-693. doi:10.1021 / acsaem.8b01715

[18] S. Wenzel, T. Leichtweiss, D.A. Weber, J. Sann, W.G. Zeier, J. Janek, Interfacial Reactivity Benchmarking of the Sodium Ion Conductors Na3PS4and Sodium β-Alumina for Protected Sodium Metal Anodes and Sodium All-Solid-State Batteries, ACS Appl. Mater. Interfaces. 8 (2016) 28216-28224. doi:10.1021 / acsami.6b10119

[19] A. Sharafi, H.M. Meyer, J. Nanda, J. Wolfenstine, J. Sakamoto, Characterizing the Li-Li7La3Zr2O 12 interface stability and kinetics as a function of temperature and current density, J. Power Sources. 302 (2016) 135-139. doi:10.1016 / j.jpowsour.2015.10.053

[20] L. Viswanathan, A. V. Virkar, Wetting characteristics of sodium on β’’-alumina and on nasicon, J. Mater. Sci. 17 (1982) 753-759. doi:10.1007 / BF00540372

[21] G.T. Hitz, D.W. McOwen, L. Zhang, Z. Ma, Z. Fu, Y. Wen, Y. Gong, J. Dai, T.R. Hamann, L. Hu, E.D. Wachsman, High-rate lithium cycling in a scalable trilayer Li-garnet-electrolyte architecture, Mater. Today. 22 (2019) 50-57. doi:10.1016 / j.mattod.2018.04.004

[22] L.C. De Jonghe, L. Feldman, A. Buechele, Failure modes of Na-beta alumina, Solid State Ionics. 5 (1981) 267-269. doi:10.1016 / 0167-2738(81)90244-7

[23] F. Han, A.S. Westover, J. Yue, X. Fan, F. Wang, M. Chi, D.N. Leonard, N.J. Dudney, H. Wang, C. Wang, High electronic conductivity as the origin of lithium dendrite formation within solid electrolytes, Nat. Energy. (2019). doi:10.1038 / s41560-018-0312-z

[24] M. Fritz, M. Barbosa, G. Staikov, W. Lorenz, M. Steinbruck, R. Knodler, Electronic conductivity of Na β″-alumina ceramics at high temperatures, Solid State Ionics. 62 (1993) 273-277. doi:10.1016 / 0167-2738(93)90382-D

[25] M. Wang, JB Wolfenstine, J. Sakamoto, Temperature dependent flux balance of the Li / Li7La3Zr2O 12 interface, Electrochim. Acta. 296 (2019) 842-847. doi:10.1016 / j.electacta.2018.11.034

[26] M.-C. Bay, MVF Heinz, R. Figi, C. Schreiner, D. Basso, N. Zanon, UF Vogt, C. Battaglia, Impact of Liquid Phase Formation on Microstructure and Conductivity of Li-Stabilized Na-β″-alumina Ceramics, (2018). doi:10.1021 / acsaem.8b01715 The citation of any document should not be construed as an admission that it is prior art with respect to the present invention.

[0062] As described above, the present invention provides a method for lowering the interfacial resistance between an electrode and a solid electrolyte and increasing the critical current density of a solid-state battery.

[0063] Although the present invention has been described in some detail with reference to specific embodiments, those skilled in the art will appreciate that the present invention may be practiced other than by the described embodiments, which are presented for purposes of illustration and not limitation. Accordingly, the scope of the appended claims should not be limited to the description of the embodiments contained herein. Various features and advantages of the present invention are set forth in the following claims.

Claims

1. 1. A method for forming an electrochemical device, the method comprising: (a) providing a precursor electrolyte having a resistive surface region, the precursor electrolyte comprising metal cation-alumina; (b) removing at least a portion of the resistive surface region; (c) thereafter, heating the precursor electrolyte to remove surface hydroxyl groups to form a solid electrolyte; (d) then contacting a side of the solid electrolyte with an electrode to form an electrochemical device; A method comprising:

2. Step (d) further comprises pressing the solid electrolyte and the electrodes together using a force in the range of 0.01 MPa to 10 MPa; The method of claim 1.

3. the electrode comprises sodium metal; The metal cation-alumina is sodium-β″-alumina. The method of claim 2.

4. The area specific resistance between the electrode and the solid electrolyte is 100 Ω cm 2 is less than The method of claim 1.

5. (e) contacting an opposing side of the solid electrolyte with a second electrode to form an electrochemical cell. The method of claim 1.

6. The critical current density of the electrochemical cell at room temperature is 2 mA / cm 2 Greater than The method according to claim 5.

7. The electrode is an anode consisting essentially of a metal selected from the group consisting of sodium, lithium, potassium, calcium, magnesium, zinc, nickel, aluminum, barium, and strontium; The method according to claim 5.

8. The metal is sodium. The method according to claim 7.

9. The second electrode is a cathode comprising an active material selected from the group consisting of layered metal oxides, metal halides, polyanionic compounds, porous carbon, and sulfur-containing materials. The method according to claim 7.

10. The electrode is an anode comprising a cationic host material; The method according to claim 5.

11. the electrode is an anode comprising a sodium host material; The sodium host material is selected from the group consisting of: (i) sodium doped silicon, germanium, tin, lead, antimony, bismuth, zinc, aluminum, titanium, cobalt, nickel, manganese, cadmium, and mixtures thereof; (ii) sodium-containing alloys of silicon, germanium, tin, lead, antimony, bismuth, zinc, aluminum, titanium, cobalt, nickel, manganese, cadmium, and mixtures thereof; (iii) sodium-containing oxides, carbides, nitrides, sulfides, phosphides, selenides, tellurides, and mixtures thereof; and (iv) carbon. The method according to claim 5.

12. The second electrode is a cathode comprising an active material selected from the group consisting of layered metal oxides, metal halides, polyanionic compounds, porous carbon, and sulfur-containing materials. The method of claim 11.

13. The area specific resistance between the electrode and the solid electrolyte is 10 Ω cm at room temperature. 2 is less than The method of claim 1.

14. the electrode comprises sodium metal; The metal cation-alumina is sodium-β″-alumina. The method of claim 13.

15. a second electrode in contact with an opposing side of the solid electrolyte to form an electrochemical cell; The method of claim 13.

16. The critical current density of the electrochemical cell at room temperature is 2 mA / cm 2 Greater than The method of claim 15.

17. The electrode is an anode consisting essentially of a metal selected from the group consisting of sodium, lithium, potassium, calcium, magnesium, zinc, nickel, aluminum, barium, and strontium; The method of claim 13.

18. The metal is sodium.

20. The method of claim 17.

19. The second electrode is a cathode comprising an active material selected from the group consisting of layered metal oxides, metal halides, polyanionic compounds, porous carbon, and sulfur-containing materials. The method of claim 15.

20. The electrode is an anode comprising a cationic host material; The method of claim 13.

21. the electrode is an anode comprising a sodium host material; The sodium host material is selected from the group consisting of: (i) sodium doped silicon, germanium, tin, lead, antimony, bismuth, zinc, aluminum, titanium, cobalt, nickel, manganese, cadmium, and mixtures thereof; (ii) sodium-containing alloys of silicon, germanium, tin, lead, antimony, bismuth, zinc, aluminum, titanium, cobalt, nickel, manganese, cadmium, and mixtures thereof; (iii) sodium-containing oxides, carbides, nitrides, sulfides, phosphides, selenides, tellurides, and mixtures thereof; and (iv) carbon. The method of claim 13.

22. The second electrode is a cathode comprising an active material selected from the group consisting of layered metal oxides, metal halides, polyanionic compounds, porous carbon, and sulfur-containing materials. The method of claim 15.

23. the metal cation-alumina is sodium-β″-alumina; The precursor electrolyte further comprises a stabilizer for the sodium-β″-alumina. The method of claim 1.

24. The stabilizer is Li 2 O, MgO, NiO, CoO, ZnO, and mixtures thereof; 24. The method of claim 23.

25. Step (a) comprises combining a first solid comprising aluminum, a second solid comprising sodium, and a third solid comprising lithium to form a mixture; and sintering the mixture to form the precursor electrolyte; 25. The method of claim 24.

26. step (b) comprises removing said portion of said resistive surface region with abrasive particles; The method of claim 1.

27. Step (c) comprises heating the precursor electrolyte at a temperature in the range of 400° C. to 1600° C.; The method of claim 1.

28. Step (c) comprises heating the precursor electrolyte at said temperature for 0.1 seconds to 5 hours; 28. The method of claim 27.

29. Step (c) comprises heating the precursor electrolyte in an inert atmosphere; 28. The method of claim 27.

Citation Information

Patent Citations

  • Beta''-alumina ceramic electrolyte and manufacture

    JP1983049660A

  • System and method for treating the surface of solid electrolytes

    WO2018184007A1

  • All-solid-state sodium ion secondary battery

    WO2019003846A1